Clinical features and psychological impact of celiac disease at diagnosis. Issue 12 (December 2021) - Zingone, Fabiana; Secchettin, Erica; Marsilio, Ilaria; Valiante, Flavio; Zorzetto, Valerio; Cataudella, Giovanni; D'Odorico, Anna; Canova, Cristina
Abstract: Background and aim: We aimed to describe the socio-demographic, behavioral and clinical profiles of adult patients with newly diagnosed celiac disease (CeD) and their possible association with QoL and psychological symptoms. Methods: Adults newly diagnosed with CeD and residents in the Veneto region were included. Their sociodemographic characteristics, clinical presentation, mode of diagnosis, duration of symptoms before diagnosis and comorbidities were recorded. All patients completed the Beck Depression Inventory (BDI), State-Trait Anxiety Inventory (STAI) and Short Form Health Survey (SF-36) questionnaires. Results: Between 2016 and 2019, 110 CeD patients (81% females, mean age 37.5) were recruited. At diagnosis, patients were categorized into classical ( n  = 56), nonclassical CeD ( n  = 49) and asymptomatic ( n  = 5) groups. Patients with classical presentation had a lower QoL than nonclassical patients, who were found to be more depressed. We observed a diagnosis delay of more than 7 months in more than 60% of patients with both classical and nonclassical presentations and we found that a longer duration of GI symptoms decreased the self-reported SF36 scores in the physical health ( p  = 0.002), social functioning ( p  = 0.03) and general health ( p  = 0.009) domains. Women had an overall lower self-perceived QoL. Conclusions: Symptomatic presentation at CeD diagnosis, diagnostic delay and sex may affect QoL and psychological disorders.